O registro inicial do documentário mineiro: Igino Bonfioli e Aristides Junqueira - Alexandre Pimenta Marques (2005)
The Initial Register of documentary Film from the state of Minas Gerais:Igino Bonfioli and Aristides Junqueira Alexandre Pimenta MarquesDissertation submitted to the Course on Visual Arts, School of Fine Arts, of the Federal University of Minas Gerais, as a partial requirement for obtaining the degre of Master in Visual Arts.Concentration Area: Art and Technology of ImageProf. Advisor. Dr.Evandro da Cunha LemosCoAdvisor Prof. Dr. Jose Tavares de BarrosBelo Horizonte School of Fine Arts / UFMG 2007AbstractThe object of this is documentary films in the silent movie, the novelty of the works of Igino Bonfioli and Aristides Junqueira, Who were contemporary film makers. The search for information on the film makers was approached through a specific aspect of documentary filmes which consited of the study of historic language in the cinema. The workinclude an initial inventory of the preserved and filed records on the pioneer film makers in Minas GeraisThe basic goal is to systematize the research documents, especially the episodes of the documentary Minas Antiga ( Ancient Minas Gerais), Igino Bonfioli and Minas Liberal (Liberal Minas Gerais) by Aristides Junqueira, along with fragments of other documentary by the same filmmakers.